2022
DOI: 10.3390/ijms23063223
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Pathways in Neurodegenerative Diseases

Abstract: Cancer and neurodegenerative diseases are two of the leading causes of premature death in modern societies. Their incidence continues to increase, and in the near future, it is believed that cancer will kill more than 20 million people per year, and neurodegenerative diseases, due to the aging of the world population, will double their prevalence. The onset and the progression of both diseases are defined by dysregulation of the same molecular signaling pathways. However, whereas in cancer, these alterations l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 245 publications
(297 reference statements)
0
11
0
Order By: Relevance
“…For instance, it is well established that "oxidative phosphorylation" is involved in PD onset and progression and that the dysregulation of the same molecular signaling pathways, such as "MAPK signaling," are implicated in the onset and the progression of cancers and neurodegenerative diseases, including PD, Alzheimer's disease, and Huntington's disease, albeit with different outcomes. 15 Moreover, pathways related to the "regulation of the actin cytoskeleton" and "focal adhesion" were also dysregulated in this study. It has been shown that these can be altered in neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…For instance, it is well established that "oxidative phosphorylation" is involved in PD onset and progression and that the dysregulation of the same molecular signaling pathways, such as "MAPK signaling," are implicated in the onset and the progression of cancers and neurodegenerative diseases, including PD, Alzheimer's disease, and Huntington's disease, albeit with different outcomes. 15 Moreover, pathways related to the "regulation of the actin cytoskeleton" and "focal adhesion" were also dysregulated in this study. It has been shown that these can be altered in neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 55%
“…For instance, it is well established that “oxidative phosphorylation” is involved in PD onset and progression and that the dysregulation of the same molecular signaling pathways, such as “MAPK signaling,” are implicated in the onset and the progression of cancers and neurodegenerative diseases, including PD, Alzheimer’s disease, and Huntington’s disease, albeit with different outcomes. 15…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of conventional oncogenic pathways are increasingly investigated in neurodegenerative disease, including AD. 53 In addition to MAPK and Ras, “PI3K-Akt signaling pathway” and “mTOR signaling pathway”, along with DEGs Cdk , Tgfb , Trp53 , and Wnt , were in our dataset and are implicated in cancer and, more recently, in AD. 53 Neuronal and synapse pathways were also represented in late-stage Pv- positive interneurons along with insulin resistance and several additional hormone pathways.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, MAPK signaling is a network that amplifies molecules promoting cell proliferation, growth, and survival. 53 Several MAPK signaling member levels are altered in AD, e.g ., p38, 54 JNK, 55 and their blockade alters amyloid burden. Mapk8 (JNK) was a DEG in our early-stage Vglut-positive dataset.…”
Section: Discussionmentioning
confidence: 99%
“…In cancers the cell survival and proliferation is increased, whereas, in NDDs those alterations lead to cell death and apoptosis. The most altered signal pathways in cancer, e.g., Nrf2 pathway and Wnt/β-catenin pathway, are also implicated in NDDs, like AD and PD ( Varela and Garcia-Rendueles, 2022 ).…”
Section: Kinase Inhibitors Used In Ndd Pathway Interrogationmentioning
confidence: 99%